2013
DOI: 10.1017/s1431927613012683
|View full text |Cite
|
Sign up to set email alerts
|

Rapid In Vitro Corrosion Induced by Crack-Like Pathway in Biodegradable Mg–10% Ca Alloy

Abstract: Abstract:The in vitro corrosion mechanism of the biodegradable cast Mg-10% Ca binary alloy in Hanks' solution was evaluated through transmission electron microscopy observations. The corrosion behavior depends strongly on the microstructural peculiarity of Mg 2 Ca phase surrounding the island-like primary Mg phase and the fast corrosion induced by the interdiffusion of O and Ca via the Mg 2 Ca phase of lamellar structure. At the corrosion front, we found that a nanosized crack-like pathway was formed along the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…6 SEM micrographs of the sample surface after the SRET measurement a, high-magnification images of the area with an active spot before b and after c the removal of corrosion products by ultrasound and SEM image of a corroded defect on the Mg-1.0Ca alloy surface d Although the etching solution used is much more aggressive than the 0.9 wt% NaCl solution, there is a same mechanism of the localized dissolution for Mg-Ca alloy. This fact is also supported by the work of Jung et al [28,51], in which it was reported that the fast corrosion of the Mg 2 Ca phase in Mg-Ca alloy is induced by the atomically exchange of O and Ca and then the corroded Mg 2 Ca phase is transformed to Mg oxides. Previous studies [15,52] showed that the fast corrosion of Mg 2 Ca phase leads to the rapid increase in Ca 2?…”
Section: Localized Corrosion Of Mg-10ca Alloysupporting
confidence: 63%
See 2 more Smart Citations
“…6 SEM micrographs of the sample surface after the SRET measurement a, high-magnification images of the area with an active spot before b and after c the removal of corrosion products by ultrasound and SEM image of a corroded defect on the Mg-1.0Ca alloy surface d Although the etching solution used is much more aggressive than the 0.9 wt% NaCl solution, there is a same mechanism of the localized dissolution for Mg-Ca alloy. This fact is also supported by the work of Jung et al [28,51], in which it was reported that the fast corrosion of the Mg 2 Ca phase in Mg-Ca alloy is induced by the atomically exchange of O and Ca and then the corroded Mg 2 Ca phase is transformed to Mg oxides. Previous studies [15,52] showed that the fast corrosion of Mg 2 Ca phase leads to the rapid increase in Ca 2?…”
Section: Localized Corrosion Of Mg-10ca Alloysupporting
confidence: 63%
“…1a of the polished surface reveals precipitate particles distributed like discontinuous network in the alloy matrix. It has been reported that the discontinuous precipitate is a eutectic micro-constituent of white color, which consists of gray a-Mg and light b-Mg 2 Ca, and the eutectic Mg has a gray color very similar to the primary a-Mg phase [28].…”
Section: Microstructure Characterizationmentioning
confidence: 99%
See 1 more Smart Citation